2014
DOI: 10.5093/cc2014a13
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la intervención del Equipo de Apoyo Social Comunitario en el FuncionamientoPsicosocial de las Personas con Enfermedad Mental Grave

Abstract: Esta novedad del recurso hace que no se cuente con datos sobre su eficacia; se propone un estudio multi-recurso que pretende demostrar la efectividad de la labor realizada por los EASC, y su impacto positivo en el funcionamiento psicosocial de las personas con enfermedad mental grave y duradera. Los resultados indican que la intervención del EASC facilita que la persona mantenga autonomía en su vida, permaneciendo en el entorno, usando menos recursos hospitalarios y cada vez más servicios de la comunidad. La s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…We eliminated 215 studies that were conducted in countries other than Ibero-America, thereby 305 studies met the eligibility conditions. We discarded 287 studies that did not involve interventions and mainly cor- The types of studies that predominated were quantitative ones (n = 13), of which nine corresponded to quasi-experimental studies (38)(39)(40)44,(48)(49)(50)(51)54), and four to experimental studies (41,43,47,53). Out of the four studies with a qualitative approach, three corresponded to case studies using a group approach (56): The first one involved information strategies through the use of social networks (55), the second and the third used a direct contact strategy between the students and the mental health service users (45,46), and the fourth included the development of a training program for professionals (51).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We eliminated 215 studies that were conducted in countries other than Ibero-America, thereby 305 studies met the eligibility conditions. We discarded 287 studies that did not involve interventions and mainly cor- The types of studies that predominated were quantitative ones (n = 13), of which nine corresponded to quasi-experimental studies (38)(39)(40)44,(48)(49)(50)(51)54), and four to experimental studies (41,43,47,53). Out of the four studies with a qualitative approach, three corresponded to case studies using a group approach (56): The first one involved information strategies through the use of social networks (55), the second and the third used a direct contact strategy between the students and the mental health service users (45,46), and the fourth included the development of a training program for professionals (51).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that gender can be a confounding variable for the results of interventions because women demonstrate a greater reduction in stigma (23). Accordingly, seven studies out of those reviewed considered this variable in their analyses (38)(39)(40)(41)(42)(43)49). Table 2 summarizes the criteria for evaluating the quality of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations